(untitled) (Journal of the Digital Humanities Association of Southern Africa, 2024)
It is with immense pride and anticipation that we introduce the fifth volume of the Journal of Digital Humanities Association of Southern Africa (JDHASA), centred on the theme “Digital Humanities for Inclusion.”